Social - Psychological Aspects of the Concept of Professional Culture of Military Personnel in the System of Ensuring Public Security - Ne'matovych, Arzikulov Dilshod (International Journal on Human-Computing Studies, 2023)
In this article, the need for psychological knowledge necessary for studying the social-psychological aspects of the concept of professional culture of national guard military personnel in ensuring public safety, as well as ways to improve professional culture and "professional knowledge, professional skills and qualifications, professional experience, professional belief, professional behavior" Concepts such as ``character'' have been theoretically analyzed such that the correct formulation of the law and legislation in the development of the society and the state serves as the main tool that ensures the non-violation of social justice.